Chronology of the western world, 1000-1500 A.D. - Erdoes, Richard; Society for Visual Education (Chicago, Ill. The Society [production company], 1984)
Examines western Europe and the rise of the Middle class, and the growing conflicts between church and state.
The March of Christianity, 1000-1250 A.D. (15 min.) -- The Age of chivalry and the renaissance, 1250-1500 A.D. (15 min.)
Keywords: Europe -- History -- 476-1492.